The Eco-Agriculture Pivoted on Maqāṣid Asy-Syarī’ah: A Qualitative Dynamic System Analysis for Food Security - Cory Vidiati; Ahmad Hasan Ridwan; Lathifaturahmah; Dini Selasi; Heru Cahyano; Irfan Safrudin; Mualimin Mochammad Sahid (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2025)
This study aims to create a sustainable and innovative agricultural ecosystem by emphasising the importance of human effort in critically assessing and sustaining their lives amid unpredictable natural conditions. By employing a dynamic qualitative approach and developing a reproducible analysis model, we gathered primary data through observations and interviews in Sarwadadi Village, Talun, Cirebon, alongside secondary data from online research publications. The findings revealed strong collaboration among farmers, local government, academics, and agricultural experts; the potential for eco-friendly and productive land use; and the establishment of a conceptual model for the qualitative dynamics of environmental conservation (fiqh al-bī’ah), which includes system analysis, problem identification, and interventions aimed at achieving desired outcomes for the future of eco-agriculture. However, this study does have its limitations, notably the omission of Vensim model analysis, which requires quantitative data.